Analisis Penguatan Karakter Religius, Terhadap Perilaku Bulliying Di Sekolah Dasar - Aisna, Rilla Nanda Riftahul; Amrullah, Muhlasin (Jurnal Gentala Pendidikan Dasar, 2025)
Digital transformation has significantly impacted students, with a noticeable rise in bullying cases, particularly among elementary school children. This study aims to analyze the influence of religious character strengthening on bullying behavior at SD Muhammadiyah 1 Sidoarjo. Using a qualitative descriptive approach, data were collected through triangulation techniques including observation, interviews, and documentation. The findings show that religious character building is implemented through daily practices such as prayer reading, moral education, the dedication of competent teachers, and participation in extracurricular activities. These efforts help students focus on personal growth and have proven effective in preventing bullying. From 30 respondents, 6.67% reported experiencing verbal bullying, 3.33% experienced social bullying, while the remaining 90% had never experienced any form of bullying. Daily habituation, instilling religious values, and teachers acting as role models play a crucial role in shaping students’ moral character and reducing bullying behavior. The results indicate that the applied methods are effective and consistent in forming students with strong religious values. However, the success of character education also depends on external support. A lack of encouragement from the surrounding environment remains a key challenge in achieving optimal outcomes in religious character development.